2007
DOI: 10.1016/j.physbeh.2006.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure to short days and low temperatures blunts stress response and yields low fluctuating asymmetry in Siberian hamsters

Abstract: Fluctuating asymmetry (FA) refers to small, non-directional deviations from perfect bilateral symmetry in morphological characters. Individuals with low FA presumably either developed in a relatively stable environment and/or were better able to buffer against developmental stressors. The present study investigated the effects of seasonal factors measured by day length and ambient temperature manipulations on the development of bilateral characters and concomitant changes in stress responses. Siberian hamsters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Some studies have found a significant correlation between fluctuating asymmetry and some environmental stressors in a variety of traits and organisms. These include temperature (Babbitt, ; Benderlioglu et al, ), population density (Serrano et al, ), poor environmental conditions (Teixeira et al, ) or minor morphological abnormalities (Polak and Taylor, ). In addition, some genetic factors like heterozygosity have also been postulated as sources of fluctuating asymmetry (FA) (Hutchison and Cheverud, ; Vangestel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found a significant correlation between fluctuating asymmetry and some environmental stressors in a variety of traits and organisms. These include temperature (Babbitt, ; Benderlioglu et al, ), population density (Serrano et al, ), poor environmental conditions (Teixeira et al, ) or minor morphological abnormalities (Polak and Taylor, ). In addition, some genetic factors like heterozygosity have also been postulated as sources of fluctuating asymmetry (FA) (Hutchison and Cheverud, ; Vangestel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding also highlights knowledge of photoperiod by the foetus. Siberian hamster neonates (P0-P21) exposed to different photoperiods and temperatures elicited sex differences in basal plasma cortisol levels, cortisol stress response, and bone length symmetry in later life (Benderlioglu et al, 2007). With regard to circadian clocks and systems development, it is interesting to note that light is detectable at the suprachiasmatic nuclei (SCN) level at P0 in wild type but not in melanopsin k/o mice as determined by FOS expression (Lupi et al, 2006).…”
Section: Perinatal Light Affects Developmentmentioning
confidence: 99%
“…Animal experiments suggest that sex differences may be important in PLICCS (Benderlioglu et al, 2007;Pyter & Nelson, 2006;Varcoe et al, 2011) and studies that attempt to demonstrate PLICCS in humans should certainly screen for sex differences where possible. Beyond collecting the usual host of established or suspected risk factors for, and co-variables of, disease developments, maternal activity patterns, breast-feeding, and maternal melatonin (and potentially other hormone) zeitgeber information to the neonate may also be important for PLICCS, although acquiring this information -at least in retrospective human studies -will be a challenge to say the least.…”
Section: "Testing" Pliccs In Epidemiological Studiesmentioning
confidence: 99%
“…Indeed, female Siberian hamsters reared in winter-like conditions with short day lengths and low temperatures in the laboratory had significantly lower cortisol concentrations in response to acute stressors and lower FA in adulthood compared to the females that were reared in any other temperature and day length groups [61]. An elevated stress response marked by increased glucocorticoids in winter months may compromise growth, immune, and other important functions that require significant energy reserves [62].…”
Section: Postnatal Development Periodmentioning
confidence: 99%
“…It should also be noted that the target group corresponded to the children who were exposed to the ice storm in utero during 14-22 weeks of gestation. Finger ridge configurations are established before the 19 th week of gestation, however [61][62][63][64]. After this period, injury and caustic substances may reduce the appearance of the ridges, but the original pattern will return unless the skin is damaged considerably [97].…”
Section: Human Studiesmentioning
confidence: 99%